High-level expression and purification of soluble recombinant FGF21 protein by SUMO fusion in Escherichia coli - Wang, Huiyan (BioMed Central, 2010)
BACKGROUND: Fibroblast growth factor 21 (FGF21) is a promising drug candidate to combat metabolic diseases. However, high-level expression and purification of recombinant FGF21 (rFGF21) in Escherichia coli (E. coli) is difficult because rFGF21 forms inclusion bodies in the bacteria making it difficult to purify and obtain high concentrations of bioactive rFGF21. To overcome this problem, we fused the FGF21 with SUMO (Small ubiquitin-related modifier) by polymerase chain reaction (PCR), and expressed the fused gene in E. coli BL21(DE3). RESULTS: By inducing with IPTG, SUMO-FGF21 was expressed at a high level. Its concentration reached 30% of total protein, and exceeded 95% of all soluble proteins. The fused protein was purified by DEAE sepharose FF and Ni-NTA affinity chromatography. Once cleaved by the SUMO protease, the purity of rFGF21 by high performance liquid chromatography (HPLC) was shown to be higher than 96% with low endotoxin level (<1.0 EU/ml). The results of in vivo animal experiments showed that rFGF21 produced by using this method, could decrease the concentration of plasma glucose in diabetic rats by streptozotocin (STZ) injection. CONCLUSIONS: This study demonstrated that SUMO, when fused with FGF21, was able to promote its soluble expression of the latter in E. coli, making it more convenient to purify rFGF21 than previously. This may be a better method to produce rFGF21 for pharmaceutical research and development.